APPLICATION OF CITY WATER BALANCE MODEL TO DEVELOP STRATEGIES FOR URBAN WATER MANAGEMENT IN HANOI - Thi Bich Ngoc, Duong; van der Steen, Peter (Journal of Forestry Science and Technology, 2016)
Urban water management is facing with a couple of problems such as inadequate water supply, untreated wastewater disposal and stormwater management. Particularly, in developing countries it seems a long way to overcome these problems. Integrated urban water management (IUWM) is considered as one of the powerful management approaches to solve those problems. This approach links water supply, wastewater and stormwater issues as one unit of management. Like many urban area in the developing world, Hanoi is dealing with pollution in receiving water bodies, ground water depletion and flooding. City Water Balance model (CWB), being used in SWITCH project, is used in this research to assess the water and contaminant balance for a typical catchment in Hanoi urban water system. A specific answer to water and contaminant flows of the catchment was clarified. A range of sustainable urban water management applications including rain water harvesting, wastewater recycling and green roof is presented. Implementation of 1m3 rainwater tank will saved 31% water supply for non-potable purposes and 540l/day of grey water recycling will be sufficient for toilet flushing. In addition, "Towards sustainability for Hanoi urban water management" strategy was proposed. Based on these findings the research is valid reference for policy-makers working on Hanoi’s water sectors.